Quality Control of the Korle Bu Rectilinear Scanner (Journal of Science and Technology, 2016)
The attainment of high standards of efficiency and reliability in the practice of nuclear medicine requires an appropriate quality assurance programme. The routine monitoring of nuclear medicine instruments, using test procedures that provide check of the quality and reproducibility of instrument performance, aims at giving the user the confidence in the data collected and in updating the performance of the instrument.Quality control testing schedule for rectilinear scanners include weekly density calibration and monthly performance contrast enhancement and collimato revaluation. Discussion in this work is however, restricted to collimator evaluation which is required to be performed at the initial stages of installation as acceptance reference. However, unlike the density, calibration and contrast enhancement, there is no documented work on this for the M800 Scintikart Scanner - a Hungarian Gamma Muvek system belonging to the Korle Bu Hospital, Accra.Tests of linearity of energy, relative sensitivity and resolution including energy and spatial resolutions were conducted. in respect of collimator evaluation. In the linearity test it was ascertained that a nonlinear relation-ship exists between the center of the window setting and the energy of the photopeak. The spectrometer was calibrated independently for each radionuclide and the position of Tc-99m obtained at .045 McV on the MeV scale. In addition, the F272 al3 Collimator offered a better resolution than the routinely used F272 al36 collimator which has the highest sensitivity.